Sodium and protein nutrition of lactating cows under tropical conditions - Thiangtum, Wandee (Wageningen University, 2018)
The objectives of this thesis were to provide a basis for improvement of milk production in small farm holders in Thailand through supplementation of protein and salt (NaCl). Four experimental objectives were identified for this research, and it was anticipated that the outcome of the research can be applied so as to improve dairy production in Thailand and potentially other countries where dairy cows are maintained under tropical conditions.